Pemfokusan Solar Water Heater Menggunakan Reflektor Parabolik - Saputro, Ego Wisnu; Ocsirendi, Ocsirendi; Saputra, Zanu (Jurnal Inovasi Teknologi Terapan, 2023)
The need for hot water is very important for the health of every human being. Not only from health, industrial fields such as hospitality have a high level of use of warm water. High usage must be balanced with existing income. However, in the case of heating water on a large scale, a large source is also needed. To overcome this, a solar water heating system was created in order to overcome this problem while at the same time utilizing natural heat sources from the sun. Solar water heaters with parabolic reflectors are made to be able to heat water by focusing light by the parabolic reflectors onto the collector pipe. In optimizing it, a tracking system for the sun is also added so that the heat absorption that occurs can be more effective. Tracking is carried out for 6 hours, starting from 09.00 to 15.00. It can be seen that the highest temperature increase uses the 10 minutes delay method of 55.18°C and the highest temperature for heating uses the continuous method of 44.62°C with the same heating time from 13.30-13.40. Comparison of the heat absorption efficiency of the collector pipe is better by using the 10 minutes delay method of 35.04% in terms of achieving the highest temperature. As for the comparison of the whole system, the use of the 10 minutes delay method has a higher efficiency of 30.95% compared to the continuous heating method.